Molecular characterization of porcine circovirus - Jaganathan, J. Seetha (2012)
A study was done to determine the occurrence of porcine circoviruses in Malaysia. Porcine Circovirus 2 (PCV2) is the causative agent of Porcine Circovirus associated Diseases (PCVAD), of which Post Weaning Multisystemic Wasting Syndrome (PMWS) is the most important. The virus is of huge economic significance worldwide. Globally, the virus and disease has been reported in Canada, US, several European countries and in Asia. In Malaysia PCV2 was first identified by the Veterinary Research Institute in 2004 by RFLP methods followed by the first case study of PCVAD in 2007 based on clinical features, histopathology findings and PCR screenings. The objectives were to detect PCV2 from selected pig farms and to genetically characterize them. Understanding the presence of the virus may contribute to better vaccination programs against the virus which may control the disease manifestation. At the time the samples were collected, PCV2 vaccines were not available in Malaysia. Therefore, this study will represent the complete phylogenetic characterization of PCV2 reported for the first time in Malaysia from samples collected in 2007. To meet the objective of the study, organ samples were collected from 42 selected pig farms in Malaysia (Penang, Perak, Selangor, Melaka,Johor and Sarawak). The organ samples were collected from animals that demonstrated typical clinical signs of PCVAD such as wasting, weight loss, stunted in growth, dyspnea, lymph nodes enlargement, diarrhea, pallor and jaundice. A total of five pigs were sampled from each farm. For the end analysis, the organs were pooled and screened by PCR to represent the data in each farm. Among the 42 farms,39 were positive for PCV, while three farms indicate negative result. Subsequently, a phylogenetic tree was constructed from 13 representative positive PCV2 samples to represent the six states of which samples were collected from. All 13 selected samples fell into the same clade as other PCV2b isolates from other countries. Amino acid sequence analysis of the putative capsid protein (ORF2) of the PCV2 revealed that there are three clusters found in Malaysia, namely cluster 1C and 1A/1B. The hyper variable regions of the ORF2 of PCV2 was analyzed by utilizing a differentiation of wild-type vs. vaccine-type strain (DIVA) assay by real-time PCR which was developed in this study in order to distinguish and differentiate the strains isolated in this study. Analysis by DIVA assay which targeted the hyper variable regions confirmed that all isolates were wild-type PCV2 with no association with vaccine strains. Overall, our study suggests that there may be a link between movements of animals by import of breeders into the country being the route of entry of the virus. However, more investigations are needed to confirm this.